2009
DOI: 10.1063/1.3167816
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the bias stability of amorphous indium gallium zinc oxide thin-film transistors using an O2 plasma-treated insulator

Abstract: The effects of an O2 plasma-treated SiNX-based insulator on the interfacial property and the device performances of amorphous indium gallium zinc oxide thin-film transistors (a-IGZO TFTs) were investigated. We tried to improve the interfacial characteristics by reducing the trap density between the SiNX gate insulator and a-IGZO channel by the O2 plasma treatment. The plasma treated-device performances were remarkably improved. The drastic improvements obtained for the O2 plasma-treated a-IGZO TFTs included ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 6 publications
1
51
0
Order By: Relevance
“…The most serious problem is the long-term stability of TFT characteristics, but recent works have achieved threshold voltage shifts of less than 2 V and even smaller than 1 V [74][75][76]. Our group has reported that thermal annealing under a wet O 2 atmosphere stabilizes the chemical bonds, leading to improved and stable TFT characteristics, and we have found that the true origin of the stability originates from the formation of acceptor-type electron traps formed under constant bias stress [77].…”
Section: Summary: Present and Future Issuesmentioning
confidence: 85%
“…The most serious problem is the long-term stability of TFT characteristics, but recent works have achieved threshold voltage shifts of less than 2 V and even smaller than 1 V [74][75][76]. Our group has reported that thermal annealing under a wet O 2 atmosphere stabilizes the chemical bonds, leading to improved and stable TFT characteristics, and we have found that the true origin of the stability originates from the formation of acceptor-type electron traps formed under constant bias stress [77].…”
Section: Summary: Present and Future Issuesmentioning
confidence: 85%
“…Especially, a-IGZO TFTs have been recognized as a very promising alternative to display backplanes of active matrix organic light emitting diodes (AMOLEDs) and thin-film transistor liquid crystal displays (TFT-LCDs) [1,2]. For practical applications, it was important to have the bias independent reliability and a number of groups have studied the stability of a-IGZO TFTs [3][4][5][6][7]. Particularly, the hump characteristics were considered as one of the critical issues during the operation in TFT displays affecting pixel brightness [8].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, there are still many issues related to the control of threshold voltage and bias-induced degradation. [6][7][8][9][10][11] Therefore, there have been many studies on improving AOS TFT stability such as high-pressure oxygen annealing, 12 annealing in hydrogen environment, 13 O 2 plasma treatment, 14 suitable passivation materials, 15 long channel TFT 16 and long-time annealing, etc. 17 Especially, the performance of a-IGZO TFT depends on channel length, and the TFTs with channel length less than 2 µm exhibit mostly depletion mode behavior.…”
mentioning
confidence: 99%